Approximation par des fractions rationelles en norme \(L^2\) (Application au filtrage numérique): Approximation by rational fractions in the \(L^2\) norm (Application to digital filtering) - Wolf, Jaques (Anal. Numér. Théor. Approx., 1981)
Not available.